Geopolitics on wheels: The repositioning of the Turkish automotive industry - Yaşar Aydın (Stiftung Wissenschaft und Politik (SWP), 2025)
Turkey is not only an important market for German automobiles - it also exports a significant volume of automobiles and components to Germany. Through their integration into German supply chains, Turkish suppliers are making a significant contribution to the international competitiveness of the German automotive industry. However, the Turkish automotive industry is facing complex economic, technological, and geopolitical challenges, including trade barriers, intensification of international competition, and macroeconomic imbalances. These challenges are now becoming more relevant for the German automotive industry as well as the country's security policy, as they pose security and geopolitical risks and could weaken ties between the countries. Turkish car manufacturers and government representatives are responding to these challenges with a strategic repositioning towards digitalisation and electrification, which is creating new opportunities for cooperation with Germany.
Keywords: 320; Turkish automotive industry; international competitiveness; trade barriers; digitalisation; electrification; Germany; cooperation"